Impact of a community-policing initiative promoting substance use disorder treatment over criminal charges on arrest recidivism. (1st October 2021) - White, Veronica M.; Avendano, Sebastian Alvarez; Albert, Laura A.; Zgierska, Aleksandra E.; Balles, Captain Joe; Zayas-Cabán, Gabriel
Highlights: Madison Addiction Recovery Initiative (MARI) is a community policing program. MARI diverts adults from criminal prosecution to addiction treatment. Referral to MARI may not reduce 6-month recidivism (i.e., arrest). Completing MARI may reduce 6-month recidivism. Among potential completers, referral to MARI may also reduce 6-month recidivism. Abstract: Background: Overdose deaths, addiction, and drug-related crime have increased in the United States over the past decade. Treatment improves outcomes, including reducing crime, but few individuals with addiction receive treatment. Here, we determine whether the Madison Addiction Recovery Initiative (MARI), a community policing program implemented by the City of Madison (Wisconsin) Police Department (MPD) that diverts adults who committed a non-violent, drug use-related crime from criminal prosecution to addiction treatment, reduces the risk of recidivism (i.e., an arrest) in the 6-month period following the index crime. Methods: Observational data were collected by the MPD for 12 months before through 6 months after an index crime from participants in the MARI program (n = 263) who referred to MARI between September 1, 2017 and August 31, 2020 and a Historical Comparison group (n = 52) who committed a comparable crime between September 1, 2015 and August 31, 2016. Average effects were estimated using intention-to-treat (ITT), a per-protocol, and a complier average causal effects (CACE) analyses, adjusted for covariates. Results: ITT analysis did not show that MARI assignment lowered adjusted odds of 6-month recidivism (aOR = 0.59 [0.32, 1.12], p  = 0.11). Per-protocol analysis showed that completing MARI lowered the adjusted odds of 6-month recidivism (aOR = 0.23 [0.10, 0.52], p  < 0.001). CACE analysis indicated that assignment to MARI among individuals who would complete the MARI program if assigned to the program lowered the adjusted odds of 6-month recidivism (aOR = 0.85 [0.80, 0.90], p < 0.001). Conclusions: Diverting adults who committed a non-violent, drug use-related crime from criminal prosecution to addiction treatment may reduce 6-month recidivism.